Torque matching of revolving vane expander and compressor - Chay, Chinq Yee (2015)
The Revolving Vane (RV) mechanism has been studied, improved and adopted onto compressor and expander for quite some time. However, it has never been investigated for the feasibility of connecting an RV compressor and RV expander together through a method called torque matching. In order to achieve the objective above, RV compressor and expander were first analysed by the means of mathematical modelling. The model consists of two parts, namely the net torque of the system and the bearing load acting on the system. The model was assumed to be a frictionless, perfectly sealed and isentropic open-cycle refrigeration system with air as refrigerant. The mathematical model was developed to numerically simulate the working principles of the compressor and expander. The average and peak torque of both the RV compressor and expander had been formulated, as well as that of the net torque and the resultant journal bearing load. It was found that the net torque of the RV compressor-expander configuration is a function of angle shifted, pressure across the vane and the rotation angular velocity. In the range of the operating conditions tested, an angle shift of about π rad leads to the most optimum point to input the minimum torque of 24.1 N.m for the cycle, except for extremely high pressure difference across the vane. In order to reduce the minimum net torque required for the system, the pressure difference across the vane should be small and the angular velocity is advisable to remain low, for example 7 bar and 1000 rpm respectively. As for the resultant bearing load, a high pressure difference such as 880 bar across the vane and angular velocity of 3000 rpm result in a large average bearing load of nearly 10000 N.